1885 From Failure to Success - A Child Protection Initiative. (October 2012) - Fraser, C
Abstract : Background and Aims: As for all child-health professionals, knowledge of safeguarding/child protection (SCP) is a key role of PICU nurses. A trust-wide audit showed deficiencies in knowledge of SCP processes in our PICU-lead centre, despite standard training. We describe the institution of a bespoke training package to address this. Methods: After a 2008 audit showed 65% compliance with SCP documentation, an internal lead nurse for SCP was appointed (CF) and lead a Transformation project entailing a series of bespoke SCP Study Days training ALL staff to Level-3 Child Protection, (recommended NHS London), on-going bi-annual updates, regular SCP information sharing and mandatory SCP induction for new starters. Repeat audits in 2010 and 2012 are reported, together with further qualitative questions (2012). Results: 30/90 PICU nurses completed each questionnaire. Repeat SCP audit showed increased compliance with SCP processes 65% (2008), 90% (2010) and 94% (2012) with 100% aware of correct SCP documentation. All staff now feel supported caring for a child with SCP concerns, and able to suggest areas for improving practice. Consultant Intensivist & lead social worker were not always identified as people who must be notified. Conclusions: We report increased SCP awareness on our PICU after a lead-nurse transformation project, with nurses now confident managing CP cases, and feeling SCP is well-managed. However, further improvement could be made in nurses interaction with the Hospital Social Care Team and further staff-support when caring for children with SCP concerns would be appreciated - especially when nurses inform parents of SCP referral.